Analytical investigation on the behavior of circular and square RC columns strengthened with RPC and wrapped with FRP under uniaxial compression. (September 2019) - Algburi, Atheer H.M.; Sheikh, M. Neaz; Hadi, Muhammad N.S.
Abstract: This paper presents an analytical approach to predict the uniaxial compression behavior of circular and square reinforced concrete (RC) columns strengthened with reactive powder concrete (RPC) jackets and wrapped with fiber reinforced polymer (FRP). The analytical axial load-axial strain responses of the strengthened RC columns were compared with experimental axial load-axial strain responses. The analytical approach presented in this study conservatively predicted the ultimate axial load of the strengthened RC columns. Also, a parametric study was carried out to investigate key factors that influence the axial load-axial strain response of the strengthened RC columns. It was found that the ratio of the RPC jacket thickness to the diameter or side length of the base RC column significantly influenced the service axial load, ultimate axial load and ductility of a strengthened RC column. Highlights: Analytical approach is developed to predict the behavior of strengthened RC columns. The strengthening technique involves jacketing with RPC and wrapping with FRP. Analytical and experimental axial load-axial strain responses are compared. Ductility and service load of the strengthened RC columns are investigated.